Effect of Curing Time on Bond Strength between Reinforcement and Fly-ash Geopolymer Concrete - Petcherdchoo, Aruz; Hongubon, Tawan; Thanasisathit, Nattawut; Punthutaecha, Koonnamas; Jang, Sung-Hwan (Applied Science and Engineering Progress, 2020)
This paper focuses on showing the effect of curing time on the bond strength between reinforcement and flyash geopolymer concrete. Various parameters are varied to compare between ordinary Portland cement (OPC) concrete and Class C fly-ash geopolymer concrete (GPC). These concretes are designed to have two different compressive strengths, and each of them is cured at 28 and 56 days. The diameter of reinforcement is selected as 12 and 16 mm with deformed type. From the study, it is found that the bond strength increase with increasing the compressive strength, while with decreasing the diameter of reinforcement, as expected. The bond strength of OPC embedded with smaller reinforcement is more sensitive to the increase of the curing time. However, its bond strength is significantly less sensitive to the compressive strength. The bond strength of GPC with higher design compressive strength is more sensitive to the increase of the curing time. However, its bond strength is significantly less sensitive to the diameter of reinforcement.